ANALISIS KEMAMPUAN KONEKSI MATEMATIK SISWA KELAS XII MADRASAH ALIYAH KOTA CIMAHI PADA MATERI SPLDV - Devina Nurdianti; Euis Eti Rohaeti; Eka Senjayawati (Journal on Education, 2019)
This research was motivated to analyze students mathematical connection skills. This research is a study that uses qualitative descriptive methods. The subjects of this study were class XII students totaling 20 students in one of the Cimahi City Aliyah Madrasas. The stages of this research start from the process of planning, implementation, and observation. The instrument question of mathematical connection ability that is given is a question that has been tested for validation by mathematicians totaling 3 questions. From the results of the research that has been carried out there are difficulties in students difficulties in solving the existing problem questions. Students who have low level of ability, difficulty factors that occur among them students have not been able to connect existing topics in mathematics, students also have not been able to understand mathematics with other sciences, and students also have not been able to apply mathematics in everyday life